Everybody wins? A discourse analysis of competing stakeholder expectations in Social Impact Bonds. Issue 3 (2nd April 2020) - Ormiston, Jarrod; Moran, Michael; Castellas, Erin I.; Tomkinson, Emma
ABSTRACT: This paper explores how diverse stakeholders frame their expectations of Social Impact Bonds (SIBs). Using discourse analysis, the authors examine competing expectations in SIB press releases, showing how they differ between stakeholders, between institutional contexts, and how they evolve over time. The paper highlights how the prioritization of social finance and collaboration discourses privileges the role of private investors, which in turn diminishes the role of service providers as innovators. IMPACT: This paper explains the competing rationales of stakeholders from different sectors and jurisdictions engaging in SIBs, and how these rationales shift over time. Policy-makers need to reprioritize the role of service providers in SIB communications as they are often marginalized in the overall public discourse—particularly in the early stages of SIB structuring. The differences the authors found between jurisdictions reveal that institutional contexts shape the nature of SIBs, and that the SIB model should not be transferred in a standardized way to differing contexts.